Development of a Simple Enzymatic Method for Screening Sucrose Content in Legume Seeds - Kim, Gyutae; Park, Aron; Kim, Woon Ji; Moon, Chang Yeok; Kang, Byeong Hee; Kim, Seong-Hoon; Choi, Yu-Mi; Ha, Bo-Keun (Plant breeding and biotechnology, 2021)
The soluble sugar content of legume seeds affects the final flavor of the legume and legume products. The purpose of this study was to develop a rapid, simple, and low-cost colorimetric method for high-throughput screening of sucrose content in legume seeds. This colorimetric method was based on the enzymatic reactions of invertase (INV) and glucose oxidase (GOD). Briefly, 20 different soybean and cowpea varieties were used in this study. For sucrose extraction, solvent-to-sample ratios of 10:1 and 5:1 were found to result in optimal absorbance values for determining sucrose content in soybean and cowpea, respectively. The extraction efficiency was also evaluated under various extraction temperatures (25℃ and 50℃) and incubation times (15 minutes, 2 hours, 8 hours, and 24 hours) and the sucrose content was found to increase with increasing temperature and time. Accordingly, the optimal extraction conditions were 24 hours of incubation at 50℃. Under this condition, the GOD/INV method had significant positive correlations (r = 0.91** for soybean and r = 0.87** for cowpea) with the high-performance liquid chromatography method. Overall, this colorimetric method is a fast, simple, and inexpensive tool for quantitative determination of sucrose content in legumes. KCI Citation Count: 0